An evaluation of the effect of managers' lack of interest in HIV/AIDS issues in the workplace, on the success of HIV/AIDS workplace programmes in the Department of Agriculture: Western Cape - Wentzel, Rashidah (Stellenbosch : Stellenbosch University, 2011)
Assignment (MPhil)--University of Stellenbosch, 2006.